Avaliaç\~ao de políticas de reduç\~ao tarifária dos sistemas de transporte público coletivo no Brasil: Evidências empíricas - Carlos Henrique Ribeiro De Carvalho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
Public transport systems have been losing demand over the last twenty years because mainly growth of individual motorized transport and the real increase in public transport fare prices. The problem is that urban mobility systems are becoming less sustainable. Transport externalities such as accidents with victims, pollution and urban congestion increase in that context. In light of the proposals to change this financing model with a view to adopting policies to reduce the price of public transport fares, the article provides empirical evidence of the economic, social and operational benefit of these policies by evaluating the case of Fortaleza-CE. This Brazilian city froze the price of their transportation charges for five years and has good results in some welfare variables.
Keywords: R48; 330; mass transit fare; urban transportation funding; urban mobility; public transport economy; transport subsidy